The Philological and Morpho-Semantic Analysis of “Ò̩ranyàn”, “Àjẹ̀sára” and “Ọmọ́lúàbí” - Adekunle, Moses Adedire; Ilori, Deborah Omolara (NIU Journal of Social Sciences, 2023)
Studies have shown that a lots of modifications and changes occurring in the Yorùbá language in the course of history. Some of the basic needed linguistics information have therefore lost in transition in diachronic overview of Yorùbá Studies. This paper uses grammaticalization theory and descriptive analysis to highlight the basic morpho-syntatic decomposition of three derived nouns viz:  “Ò̩ranyàn, Àjẹsára” and “Ọmọlúàbí”. Adopting the four major parameters proposed by Bernd and Heiko (2012) as in: Extension, Desemanticization, Decategorialization and Erosion, the study argued that the basic intuitive knowledge in the memory of many Yoruba speakers seems erroneous. Our findings revealed that the three (3) words under the study –“Ò̩ranyàn, Àjẹsára” and “Ọmọlúàbí” have the basic morpho-syntactic formation in the following sequences as in: (i) oranyàn  “ò̩ran yíyàn”, (ii) “Àjẹséra – À-jẹ-sé-ara” and (iii) “Ọmọlúàbí – Ọmọ-o-ní-ìwà ìbìlẹ̀”. Also, “oran yíyàn” which basically simply means “something one has an option for” has been accorded a new meaning as in: “obligatory matter”. The paper therefore aimed at correcting the age-longed misconception and misinterpretation of the three words. We believe further studies could be done to challenge some erroneous intuitive knowhow of the basic formation of some other Yorùbá words in the contemporary usage. Keywords: Psycho-linguistic intuition, etymo-semantics, grammaticalisation, desemanticization, decategorisation, erosion.